Pembuatan Film Pendek Berjudul ‘Jangan Menyerah’ Dengan Menggunakan Kamera Smarphone - Darmoyo Darmoyo (Journal of Information System and Technology (JOINT), 2020)
Capturing and recording images in making a film is not only done by pro cameras such as various kinds of camcorder video cameras and DSLR-type video cameras. In addition to its use requiring special expertise for the wearer, the video camera has various features or parts that are rather complicated in its operation and settings. The presence of video cameras found on smart phones, can provide an alternative for users in the process of taking and recording images that are more practical, fast and efficient. Although the results of images or videos produced through smart phone video cameras are not as good as when compared to using a more pro video camera. "The Making of A Short Movie ‘Jangan Menyerah’ using Smartphone Camera", shooting is done using a Samsung Galaxy J5 (2016) smart phone video camera with a cinematography method that goes through the video editing process using the Sony Vegas Pro 11.0 application. The results of the video in the form of short films then distributed publicly on the Youtube channel which are expected from the short film can be an interesting and entertaining film and can provide motivation to the audience to make a change.